HUBUNGAN ANTARA PERAN GURU PAMONG DAN MINAT MAHASISWA MENJADI GURU DENGAN PRESTASI PROGRAM PENGALAMAN LAPANGAN (PPL) : Studi Kasus Pada Mahasiswa Pendidikan Akuntansi FKIP-UMS - Sami'an, Sami'an; Premana, Analya (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
The aim of the research is to know the relation of teacher consultant and students’interest to be teacher with (PPL) field experience program achievement ofeconomics accounting education students, FKIP UMS, in 2008 – 2009 academicyear. The kinds of research is descriptive qualitative and population used is all EconomicsAccounting Education students, FKIP UMS, in 2008 – 2009 academic year totally 150students. Sample taken is 105 by using random sampling technique. Data collection used arequestionaire and documentation, while data analysis used doubled linear regression analysistechnique. Doubled linear regression test (F test) and doubled linear regression coeficienttest (T test), and then relative contribution and effective contribution computation were done.The research result showed that the role of consultant teacher and students’ interest to beteacher have positive and significant influenced to PPL achievement, both partially orcomulatively. Consultant teacher role variable gave effective contribution 23,60%. Students’Interest to be teacher variable gave contribution 32,30%. Totally effective contribution is55,90%, while the rest is 44,10% was influenced by another variable.